Penerapan Model Pembelajaran Langsung (Direct Instruction) Untuk Meningkatkan Kreativitas Siswa Di Sd Gmim 7 Tomohon - Ester, Kartini; Pamase, Dwi Andriani; Paputungan, Fidinda Andriani; Elias, Sity Musdaliva; Polii, Intania Andriani; Suak, Kevin Yosua (Jurnal Ilmiah Wahana Pendidikan, 2023)
The Direct Learning Model is a teaching approach that is specifically designed to support students' learning processes related to descriptive knowledge and procedural knowledge that is well structured and can be taught with a gradual activity pattern. The aim of the Direct Learning model research is to improve students' skills and creativity in drawing. The method used in this research is Classroom Action Research (PTK). The data collection techniques used were observation and interviews. The data collection instrument in this research was the student observation sheet. In this research, students were asked to create works in the form of imaginative images. In making imaginative images they are given the freedom to express their ideas and imagination. The subjects in this research were 3rd grade students at SD GMIM 7 Tomohon for the 2023/2024 academic year with a total of 40 students. The results of this research indicate that the direct learning model can be an effective model for improving students' skills and creativity in making imaginative drawings for grade 3 students at SD GMIM 7 Tomohon.